WORKING MEMORY AND SIMULTANEOUS INTERPRETING - Bektemirova Beknozakhon Bakhtiyorjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This paper presents a theoretical overview of the concept of working memory capacity and its practical role in interpreting. Two selected types of studies indicate the empirical approaches to researching the effect of working memory and training. Finally, suggestions are made for further future research to examine the other functions of working memory in interpreting.